2020
DOI: 10.37936/ecti-eec.2020181.210333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Improvement of Ventilation System Inside Low-Cost Automation Line to Reduce Particle Contamination

Abstract: A Low-Cost Automation (LCA) line, a group of machines to manufacture hard disk drive's components located inside a clean room of factory, faces the problem of particle contamination caused by an improper ventilation system. To solve this problem, Computational Fluid Dynamics (CFD) has been implemented to evaluate airflow and simulate solutions to improve the ventilation system of the LCA. By using actual operating conditions collected at the factory and Fluent CFD software, the simulation showed that airflow p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For the turbulence equation, the shear stress transport (SST) k-ω turbulence model was chosen, as in [1,[20][21][22][23]. The SST k-ω equation can be written as…”
Section: Aerodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the turbulence equation, the shear stress transport (SST) k-ω turbulence model was chosen, as in [1,[20][21][22][23]. The SST k-ω equation can be written as…”
Section: Aerodynamicsmentioning
confidence: 99%
“…where µ is the molecular dynamics viscosity, P k is the shear production of turbulence, µ t is the eddy viscosity, ω is the specific dissipation rate, k is the turbulent kinetic energy, F 1 is the blending function, and α, β, σ are the specific coefficients for the SST k-ω turbulence model. Further details and definitions of the parameters can be found out in [1,[20][21][22][23]. The ANSYS CFX software can calculate the AD, C l , C d , and pressure, via Equations (1)- (5).…”
Section: Aerodynamicsmentioning
confidence: 99%
“…From the calculation based on the actual conditions at the factory, we found that the Reynolds numbers (Re) were between 5 × 10 3 -2 × 10 5 , which matched the SST k-ω turbulence model. The SST k-ω equations can be written as [6][7][8]12,25,27]:…”
Section: Sst K-ωmentioning
confidence: 99%
“…First, the key is to change the airflow, air change rate, the layout of the machine installation, etc., of the cleanroom [2][3][4] and wear the proper uniform of operators [5]. For the latter, the solution can be obtained by changing the conditions of the air circulation system, especially in the machines [6], installing the fan filter unit [7], modifying the hood's shape [8,9], and adding the cleaning process [10][11][12]. In brief, the global and local exhaust ventilations consist of three main components: suction head or hood, duct, and vacuum pump.…”
Section: Introductionmentioning
confidence: 99%